DEINKABILITY OF SOY INKJET INK PRINT BY MODIFIED INGEDE METHOD USING SOY OLEIC ACID - (:unkn) unknown (EDITURA ACAD ROMANE, 2017)
A soy protein-based cyan inkjet ink was formulated. The obtained inkjet ink was printed using an Epson WF-2540 inkjet printer on office paper. Deinking of the soy protein-based water-based inkjet ink prints was performed using a modified version of the INGEDE method with soy-based fatty acid. Fatty acid extracted from food grade soybean oil was employed in one-loop flotation deinking of soy-based inkjet printed paper. The extracted fatty acid had varied acid and saponification numbers. The effect of the soy oil fatty acid on inkjet ink printed paper deinking was studied. Deinking results are compared to INGEDE 11p procedure, using oleic acid. It was discovered that the laboratory formulated soy ink is deinkable using both standard and modified INGEDE method with similar results.
Keywords: soy-based inkjet; ink; soy oleic acid; deinking; INGEDE method; DEINKING; PAPER